Unveiling the Knowledge Frontier: A Scientometric Analysis of COPD with Sarcopenia - Zou J; Peng W (International Journal of COPD, 2024)
Jingfeng Zou, Wen Peng Department of General Practice, Union Hospital, Tongji Medical College, Huazhong University of Science and Technology, WuHan, Hubei, People’s Republic of ChinaCorrespondence: Wen Peng, Department of General Practice, Union Hospital, Tongji Medical College, Huazhong University of Science and Technology, Jie Fang avenue, WuHan, Hubei, 1227, People’s Republic of China, Email pengwen666@sina.comObjective: Numerous articles and reviews addressing the intersection of Chronic Obstructive Pulmonary Disease (COPD) with sarcopenia have been documented. However, a significant gap exists in the literature concerning scientometric analysis in this field. This study aimed to concentrate on recent research and elucidate emerging research areas through the examination of COPD with sarcopenia.Methods: Articles in the field were systematically retrieved from the Web of Science Core Collections (WoSCC) spanning from 2003 to 2022. The analysis employed scientometric and keyword analyses through specialized software, including VOSviewer, CiteSpace, and Origin.Results: A comprehensive analysis of 758 articles and reviews in the field of COPD with sarcopenia revealed the United States as the leading contributor in terms of publications and overall influence. Maastricht University emerged as the most prolific institution, with Schols Annemie M. W. J. being identified as the most influential scholar in this field. The International Journal of Chronic Obstructive Pulmonary Disease emerged as the most prolific journal. Notably, COPD with sarcopenia exhibits frequent associations with other diseases, underscoring the complexity of the topic and emphasizing the necessity for comprehensive treatment. Mechanistic and diagnostic aspects, particularly computed tomography, are pivotal in this research field. Osteoporosis emerges as a prospective avenue for future research, encompassing both COPD and sarcopenia. Furthermore, nutrition and physical activity are integral components for managing COPD patients with sarcopenia.Conclusion: This study delineates the distribution of fields, the knowledge structure, and the evolution of major research topics related to COPD with sarcopenia. The identification of keyword hotspots enhances the understanding of the occurrence, development, and future study trends associated with the topic.Keywords: chronic obstructive pulmonary disease, COPD, sarcopenia, scientometric analysis, visualization